The Brain Drain : Some Evidence from European Expatriates in the United States - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2004)
This paper uses U.S. Census data from 1990 and 2000 to provide evidence on the labor market characteristics of European-born workers living in the US. It is found that there is a positive wage premium associated with these workers, and that the highly skilled are overrepresented compared with the source country, more so when one moves up the skill ladder.
Keywords: J61; J31; 330; brain drain; migration; Europe; Brain Drain; Internationale Arbeitsmobilität; Migranten; Europäisch; Lohnniveau; Vereinigte Staaten